Factors that Influence Consumer Purchase Intention: A Case Study of 99 Speedmart in Malaysia - Tan, Seok Theng; Tan, Suk Yi; Tan, Su Chi; Tan, Wei En; Abdullan, Manar; Khadran, Reem; Sharma, Sweety (AIBPM Publisher, 2022)
99 Speedmart is recognized as a fast-growing chain of delectable mini-markets because of its intense focus on customer satisfaction, aggressive responsiveness, and marketing strategies. This study investigates the factors that influence the customer purchase intention at 99 Speedmart. We examine five key factors, namely perceived usefulness, perceived trust, perceived convenience, customer satisfaction, and customer loyalty, and how these five factors influence consumer purchase intention. Besides, we examine if perceived usefulness, trust, convenience influence customer satisfaction, and loyalty. We also intend to identify if customer satisfaction influences customer loyalty. A total of 150 respondents were collected, and data were analyzed using SPSS. The findings revealed that perceived usefulness and perceived convenience have a direct positive relationship with purchase intention. Besides, perceived usefulness, trust, and convenience positively influence customer satisfaction, while only perceived trust directly influences customer loyalty. Customer satisfaction was found to have a direct link to customer loyalty. This study provides new insights on the topic of consumers' purchase behavior.Â Keywords: 99 Speedmart, Customer Loyalty, Customer Purchase Intention, Customer Satisfaction, Malaysia, Perceived Convenience, Perceived Trust, Perceived Usefulness